Prove that 1*2 + 2*3 + 3*4 + ... + n(n+1) = (n(n+1)(n+2))/3

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To prove the statement `1*2+2*3+3*4+cdots+n(n+1)=1/3n(n+2)(n+2)`  we need to use induction.

First, let n=1.

The left side is `1*2=2`

The right side is `1/3 1(2)(3)=2` so the statement is true for n=1.

Now assume `n=k` is true.

Then, we need to use that statement to show that `n=k+1` is also true, and by the principle of induction, means that the statement is true for all n.

For n=k+1, we need to show that

`1*2+2*3+3*4+cdots+n(n+1)+(n+1)(n+2)=1/3(n+1)(n+2)(n+3)`

`LS=1*2+2*3+3*4+cdots+n(n+1)+(n+1)(n+2)`  use induction for n=k

`=1/3n(n+1)(n+2)+(n+1)(n+2)`   simplify

`={n(n+1)(n+2)+3(n+1)(n+2)}/3`   

`=1/3(n+1)(n+2)(n+3)`

`=RS`

By induction, the statement is true.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial